A scholastic outbreak of tinea due to Trichophyton soudanense in Italy. - Di Landro, A.; Grossi, A.; Pesenti, G.; Costa, G.; Passera, M.; Cuoco, E.; Amato, V. (European Journal of Pediatric Dermatology, 2010)
A scholastic outbreak of tinea capitis and corporis was reported. Overall 24 cases were identified, all children attending a nursery school in a small town placed in the south of the province of Bergamo, in the center of Lombardy, one of the most populated Italian regions, with a high percentage of immigrants (7% of the population). Index patient was a little boy of Nigerian origin. Mild inflammatory signs and negativity of first microscopic observation delayed adequate case treatment. Trichophyton soudanense was identified as causative agent. A first outbreak of tinea capitis and corporis, with 12 affected children plus index case, was followed, after summer holidays, from a new spreading of infection, with 11 cases. Increasing infections from anthropophilic dermatophytes in Italy as in other European countries are mainly related to social changes due to migration.